Vírus sincicial respiratório humano em pneumonias adquiridas na comunidade em dois anos consecutivos de vigilância (2010 e 2011)em um hospital infantil de Fortaleza. - Oliveira, Sabrynna Brito (2014)
The Human Respiratory Syncytial Virus (HRSV) is the leading cause of acute respiratory infection, lower respiratory tract infections in children under five years old viral agent. The example of these infections can quote the Community Acquired Pneumonia (CAP) is the leading cause of death among infectious diseases in this age group. Correct identification of the causative agent of CAP is important for the institution of correct treatment, thus avoiding the misuse of antibiotics and preventing hospital infections. The objectives of this study were to assess the percentage of detection of HRSV in cases of CAP in the city of Fortaleza, Ceará - Brazil, in the years 2010 and 2011 through the immunofluorescence assay (IFA) and polymerase chain reaction preceded transcription reverse viral RNA (RT-PCR), and check for significant differences in the epidemiology and seasonality of HRSV compared the results between techniques. Of the 483 samples of CAP, 195 (40.37 %) were diagnosed in 2010 and 288 (59.63 %) in 2011. Of the total, 55 samples (11:38 %) were positive for HRSV by IFA technique and 97 (20.8%) by RT - PCR. A significant increase of 43.29 % in total samples positive for HRSV by RT-PCR when compared to the IFA technique (p = 0.0000). RT - PCR showed a sensitivity, specificity, agreement and positive and negative predictive value of 94.54 %, 89.48 %, 62.82 %, 53.60 % and 99.22 % respectively. It was observed that HRSV did not follow the same seasonal pattern when comparing the years 2010 and 2011. Positive cases 2011 occurred mainly in the months of March and April , three months before the 2010 positive cases , which occurred in the months of May, June , July and August (p = 0.0000). It was observed that the peak positive was correlated with the rainy season, but not necessarily all peaks of rainfall of the year in which the positive and even between both techniques showed peaks at different months. The occurrence of HRSV in Fortaleza showed a seasonal pattern associated with the rainy season for both techniques. The RT -PCR was more sensitive in detecting cases of CAP caused by HRSV compared to the IFI , enabling better identification of the viral agent and allowing a better characterization of the extent of the epidemic virus periods.